The Application of Wise Family Financial Management to Improve Household Welfare - Zakiroh, Ainin; Lahmadini, Ersha Karima; Salsabila, Hana; Purnama, M. Wildan; Fajriyah, Nuniek Nizmah; Setiawan, Sigit Adi; Slamet, Slamet (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2025)
Wise management of family finances is an important factor in maintaining economic stability and household welfare, especially during economic uncertainty. Kwagean Village, Wonopringgo Sub-district, Pekalongan District, is an area where many families rely on small businesses and the informal sector, such as convection. However, financial management challenges often make it difficult for families to prioritize their needs and cope with daily economic pressures. Therefore, education and assistance on effective financial management are needed. The purpose of this community service is to increase families' knowledge and skills in Kwagean Village, Wonopringgo Subdistrict, Pekalongan, in conducting sound family financial management to improve their welfare and economic resilience amid dynamic economic conditions. This community service is delivered through interactive counseling and hands-on training that actively involves residents. The community service activities were held at one resident's house for one day, with participants from various families and youth groups. The facilitators were KKN students from Universitas Muhammadiyah Pekajangan, Pekalongan, who used a communicative, easy-to-understand approach and provided real examples tailored to local conditions. Participants understood how to manage finances in a more planned manner, live frugally, as well as